2016
DOI: 10.1111/anu.12419
|View full text |Cite
|
Sign up to set email alerts
|

Comparative growth and survival of spat of the Caribbean pearl oyster,Pinctada imbricatacultivated indoor with microalgae diets and outdoor with natural diet

Abstract: We report the results of survival and growth in size and dry mass of spat of the Caribbean pearl oyster Pinctada imbricata cultivated under outdoor (field culture) and indoor (Laboratory) conditions. Field group fed on environmental seston. Laboratory groups were fed with mono, binary and ternary mixtures of three cultivated algae: Isochrysis galbana (Ig), Tetraselmis chuii (Ig) and the Chaetoceros sp. (Ch-A, isolated from north-eastern Venezuela). After 30 days of trial, fatty acid profiles of spat were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(70 reference statements)
1
3
0
1
Order By: Relevance
“…have better growth performance (Esquivel and Lobina, 1994). Furthermore, the same results was also observed in Argopecten ventricosus (Lora-Vilchis and Doktor, 2001), Pinctada imbricata (Lodeiros et al, 2016), and Ostrea edulis (Laing and Millican, 1986. ) Although in other species of mollusk, I. galbana showed better result in inducing growth of M. mercenaria (Wikfors et al, 1992) and C. virginica (Epifanio, 1979).…”
Section: Resultssupporting
confidence: 61%
“…have better growth performance (Esquivel and Lobina, 1994). Furthermore, the same results was also observed in Argopecten ventricosus (Lora-Vilchis and Doktor, 2001), Pinctada imbricata (Lodeiros et al, 2016), and Ostrea edulis (Laing and Millican, 1986. ) Although in other species of mollusk, I. galbana showed better result in inducing growth of M. mercenaria (Wikfors et al, 1992) and C. virginica (Epifanio, 1979).…”
Section: Resultssupporting
confidence: 61%
“…Early studies recognised lipids to be the main energy stores for bivalves up to 6 months post-settlement [25,26]. Since then, evaluating the lipid composition of diets and juveniles gained a central importance on bivalve nutrition studies with examples available for clams [27][28][29][30][31][32][33], scallops [34][35][36], oysters [37][38][39][40][41][42] and mussels [19,[43][44][45][46]. Other than protein and carbohydrate composition, the nutritional properties of shellfish diets strongly depend on the essential PUFA (arachidonic acid-20:4n-6, AA; eicosapentaenoic acid-20:5n-3, EPA; docosahexaenoic acid-22:6n-3, DHA) content [47].…”
mentioning
confidence: 99%
“…Suitable particle sizes for P. f. martensii and P. maxima are 2.5-10 μm and >4 μm, respectively (Yukihira and Klumpp, 1999;Tomaru et al, 2002). Although the microalgae of all sizes used in this study could be easily ingested, smallsize microalgae [I. galbana (I, ~5.51 μm) and C. muelleri (C, ~4.5 μm)] were more suitable for these two pearl oyster species 2002; Lodeiros et al, 2017). In our study, the crude protein and lipid in the I and C groups were higher than those in the P group, which indicated that more nutrients are obtained by pearl oysters from I and C treatments.…”
Section: Discussionmentioning
confidence: 87%